R&D and employment: some evidence from European microdata - Bogliacino, Francesco; Piva, Mariacristina; Vivarelli, Marco (Bonn, 2011)
"After discussing theory regarding the consequences of technological change on employment and surveying previous microeconometric literature, our aim with this paper is to test the possible job creation effect of business R&D expenditures, using a unique longitudinal database covering 677 European manufacturing and service firms over the period 1990-2008. The main outcome from the whole sample dynamic LSDVC (Least Squared Dummy Variable Corrected) estimate is the labour-friendly nature of companies’ R&D, the coefficient of which turns out to be statistically significant, although not very large in magnitude. However, the positive and significant impact of R&D expenditures on employment is detectable in services and high-tech manufacturing but absent in the more traditional manufacturing sectors. This means that we should not expect positive employment effects from increasing R&D in the majority of industrial sectors. This is something that should be borne in mind by European innovation policy makers having employment as one of their specific aims. "